Pemanfaatan Limbah Cair Tahu Sebagai Bahan Baku Alternatif Gas Bio - Dita Yuliana; Sri Muryani; Agus Kharmayana Rubaya (Poltekkes Kemenkes Yogyakarta, 2008)
The liquid waste yielded from soybean curd industry owned by Mr. Sudaryanto has not been adequately processed before discarded into water body. As the result, some people who living nearby felt annoyed. On the other hand, the li-quid waste contains relatively high organic substance which can be utilized as raw material for bio gas production. The objective of the study was to produce bio gas from the utilization of soybean curd liquid waste. It was expected that the bio gas would have similar characteristics with those made from cow ma-nure. By using “Post Test Only Control Group Design”, the collected data from this true experimental study was analyzed descriptively, as well as analytically by using unpaired t-test at 0,05 significance level; meanwhile, to analyze the results two parameters were selected i.e the time needed to forming and the quantity of the bio gas. As the results: there was no difference between the time needed to forming the bio gas made of soybean curd liquid waste and that of cow manure (p-value = 0,069); however, there was a difference between the quantities of the bio gas made of both raw materials (p-value = 0,036).